Energy drink consumption is associated with unhealthy dietary behaviours among college youth. (November 2015) - Poulos, Natalie S; Pasch, Keryn E
Aim: Energy drink consumption has been associated with a variety of health risk behaviours, yet little research has explored the relationship between energy drinks and dietary behaviours of emerging adults. Therefore, the purpose of this study was to explore the relationship between energy drink consumption and dietary behaviours among energy drink users and non-users within a sample of college youth. Methods: College freshmen ( n  = 585, m age = 18.7 years; 47% non-Hispanic White, 20.9% Hispanic, 25.5% Asian, 2.7% non-Hispanic Black and 4.4% other; 56% female), at a large, southwest university self-reported their energy drink consumption in the past week and a variety of dietary behaviours, including past week soda, diet soda, pre-packaged salty snacks, pre-packaged sweet snacks, fast food, restaurant food, frozen food, fruits, vegetables, milk and breakfast consumption. Linear regression analyses were run to determine associations between energy drink consumption and dietary behaviour among users and non-users of energy drinks. Analyses controlled for gender, race/ethnicity and body mass index (BMI). Results: Overall, 17.5% of students had consumed energy drinks in the past week. Energy drink users were more likely to be male, White and have a greater BMI. Students also reported low past week intake of fruits, vegetables, milk and breakfast. Past week energy drink consumption was associated with increased soda and frozen meal consumption. Conclusion: Given a rapidly expanding energy drink market, future dietary interventions among college youth may want to consider the implications of energy drinks, as results of this study suggest consumption of these beverages is associated with unhealthy dietary behaviours and a greater BMI.